The effects of different mastery criteria on the skill maintenance of children with developmental disabilities. Issue 3 (3rd June 2019) - Richling, Sarah M.; Williams, W. Larry; Carr, James E.
Abstract : The acquisition of skills by individuals with developmental disabilities typically includes the attainment of a certain mastery criterion. We conducted a survey of practitioners who indicated the most commonly used mastery criterion as 80% accuracy across three consecutive sessions. Based on these results, we conducted a series of three experiments to evaluate the relation between mastery criterion and subsequent skill maintenance with 4 individuals with various developmental disabilities. Results suggest that 80% accuracy across three consecutive sessions may be insufficient for producing maintenance in some cases.